Studi Estetika Teologis Tentang Kematian Dalam Terang Berpikir Arthur Schopenhauer - Krye Nikho Pagalla; Alfri Tandi; Santi Ribka; Agnes Fiadolorosa; Katrina Friskia (Lembaga Pengembangan Kinerja Dosen, 2024)
The people of Kalambe Fort understand that death was caused by sins committed by the first humans who were placed in the Garden of Eden. Sin creates a wall of separation between humans and God, resulting in humans experiencing death. The presence of Christ breaks down the wall of separation between humans and God, namely sin. Through the death and resurrection of Christ as a sign that Christ has defeated death and humans gain the freedom to gain life after death. However, some members of the Fort Kalambe' congregation are still drowning in grief when facing death. The method used in this research is the Qualitative Phenomenology method where the author describes life in the congregation, describing phenomena that occur in the field, using Arthur Schopenhauer's theory which considers aesthetics to be a path to liberation of the will. The results of this study state that the worry about grief events is the congregation's fear of being abandoned by their beloved family. The congregation remains hopeful in the resurrection of Christ, and sorrow can disappear when people can let go of their will not to harbor thoughts and feelings for people who have gone.